THE INFLUENCE OF HR QUALITY ON PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE FOR BPJS EMPLOYEES IN THE SUMBAGUT AND REGIONAL OFFICES RANGE OF BRANCH ALL OFFICES MEDAN RAYA - Dika Arya Perdana; Kiki Farida Ferine (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This study aims to see the effect of HR quality on performance through job satisfaction by conducting research using associative quantitative research, where the research is in the BPJS Ketenagakerjaan office in the Sumbagut area and all branch offices in Medan, the employee population is 130 and the sample is 98 using the technique slovin to find samples. The research model used was path analysis and data collection techniques were questionnaires and surveys. Based on the results of the research that has been done and data analysis as explained in the previous chapter, the following conclusions are conveyed from the results of the research as follows: Job satisfaction has a positive and significant effect on performance, this can be proven in Path Coefficients with an original sample of 0.250 and P values 0.008 < 0.05. HR quality has a positive and significant effect on job satisfaction, this can be proven in the Path Coefficients with an original sample of 0.699 and P values 0.000 <0.05. HR quality has a positive and significant effect on performance, this can be proven in the Path Coefficients with an original sample of 0.441 and P values 0.000 <0.05. Job satisfaction can be an intervening variable and has a significant positive effect. This can be proven in the Path Coefficients with an original sample of 0.174, P value 0.009 <0.05.